2008
DOI: 10.1186/1475-2875-7-129
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of immunoglobulin purification methods and their impact on quality and yield of antigen-specific antibodies

Abstract: Background: Antibodies are the main effectors against malaria blood-stage parasites. Evaluation of functional activities in immune sera from Phase 2a/b vaccine trials may provide invaluable information in the search for immune correlates of protection. However, the presence of antimalarial-drugs, improper collection/storage conditions or concomitant immune responses against other pathogens can contribute to non-specific anti-parasite activities when the sera/plasma are tested in vitro. Purification of immunogl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 25 publications
1
40
0
Order By: Relevance
“…As parasite-targeted antibodies, functional Plasmodium-specific IgGs isolated from immune sera could be effective. However, the quality, quantity, and functional activity of IgGs recovered from animals experimentally immunized with recombinant parasite antigens or from humans endemically exposed to malaria are highly dependent on the purification method and the species (Bergmann-Leitner et al 2008). In the present work, the high-affinity chromatography system used to purify IgGs proved to be adequate for the isolation of high quality functional IgGs from malaria-resistant mice, as indicated by their electrophoretic profile and their reactivity against P. yoelii proteins.…”
Section: Discussionmentioning
confidence: 99%
“…As parasite-targeted antibodies, functional Plasmodium-specific IgGs isolated from immune sera could be effective. However, the quality, quantity, and functional activity of IgGs recovered from animals experimentally immunized with recombinant parasite antigens or from humans endemically exposed to malaria are highly dependent on the purification method and the species (Bergmann-Leitner et al 2008). In the present work, the high-affinity chromatography system used to purify IgGs proved to be adequate for the isolation of high quality functional IgGs from malaria-resistant mice, as indicated by their electrophoretic profile and their reactivity against P. yoelii proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Yoon et al used a different method for determination of a conversion factor (34), and Bergmann-Leitner et al have shown that the total IgG purification method affects the growth-inhibitory activity (1). In addition, as we showed previously with an AMA1 vaccine in rabbits (20), the AMA1 combination vaccine (FVO plus 3D7) induced more crossreactive antibodies than a single-allele vaccine, and the growthinhibitory activity of the cross-reactive antibody was slightly weaker than that of strain-specific antibody when antibody titers were normalized.…”
Section: Discussionmentioning
confidence: 99%
“…[15] The importance of a suitable purification method for immunoglobulins was discussed by Bergmann-Leitner et al with a concluding remark that the efficiency of a purification method differs on the species of IgG donors; the purification itself did not affect the avidity of MSP-I 42 specific antibody but influenced its biological activity depending on the method used. [16] Alteration of Antibody Specificity During Isolation and Storage 55…”
Section: Discussionmentioning
confidence: 99%